Analysis of the Strengths and Weaknesses of Employing Foreign Workers at Company X - Pratama, Vazly Arris; Hakim, Azis (Jurnal Indonesia Sosial Sains, 2025)
The purpose of this study was to determine the advantages and disadvantages of using foreign workers in company X. The research method used was qualitative research. Data collection techniques were carried out through observation, documentation, and interviews with 10 sources consisting of officials and workers in the company, both foreign and local workers. The research data that had been collected was then analyzed in depth. The results of the study showed that the use of foreign workers had several advantages and disadvantages. The advantages are that foreign workers who have the skills needed by the company, have broad insight to come up with new ideas as company innovations and increase the company's value in front of both national and international clients. While the disadvantages are that the use of a single workforce requires high costs, cultural and language differences create a difficult level of adaptation, cause a lot of unemployment in the country, and regulatory changes that do not cause companies to be alert to various regulatory changes regarding the use of foreign workers in their companies. Therefore, the use of foreign workers must be carried out wisely according to the company's capabilities and needs while still considering the quality of domestic workers.